Phenotipical Characters of Melon (Cucumis melo L.) in Response to Karst Critical Land - Yuanita Rachmawati; Budi Setiadi Daryono; Ganies Riza Ariestya (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2018)
Yogyakarta Agroecosystem has 158,600 ha of critical land spread over three zones. Two areas are Karst Land, located on Agroecosystem II includes Gunungsewu Hills, Gunungkidul and III covers Dlingo Bantul Hills and Sentolo Hills Kulon Progo Regency.. Karst Land is certainly provides stress to plants. These research purposes are examining the phenotype character of superior melon Cultivar TACAPA compare to parents and offsprings phenotypes. The phenotype characters are based on plant height, leaf number, time of melon flowering, water content of plants, and fruit and seed productivity. This experiment was done by Split Plot Design with Completely Randomized Design (CRD) with 4 kinds of treatment (control plant media, Gunungsewu, Dlingo, and Sentolo), 7 experimental units cultivars: TACAPA, TA, TP, PT, AT, Action 434, PI 371795), and 4 replications. Research result reveals that most of the phenotypic characters including plant height, number of leaves, fruit weight, and number of seeds produced have relatively no significant effect between treatment and control, while the phenotypic first time flowering time and water content of the plant, have a noticeable difference.